Annealing Effects in Low Temperature Amorphous Silicon Flexible Solar Cells. (December 2015) - Wilken, K.; Finger, F.; Smirnov, V.
Abstract: We report the effects of prolonged post-deposition annealing on the performance of amorphous silicon (a–Si:H) solar cells and single layers, that are fabricated at low temperature of 120 ̊C on flexible PET and glass substrates. These low temperature solar cells show a significant improvement in performance upon post-deposition annealing (up to two hours) in all parameters of the current-voltage (JV) curves of the solar cell, resulting in an efficiency increase up to 34% (relative). Comparison of external quantum efficiencies of p- and n-side illuminated cells, as well as varied absorber layer thicknesses and reverse bias voltage, suggest that the collection of minority carriers are mainly improved upon annealing. Both the increase of the built-in field in the solar cell and improvement in the electronic properties of the absorber layer were found to contribute to an improved carrier collection and solar cell performance.